(untitled) (Nigerian Journal of Pharmaceutical Research, 2022)
Background: Wound infection is the third most common nosocomial infection worldwide, with resultant high mortality and morbidity rates in developing countries. Many pathogenic microrganisms implicated in wound infections have evolved antimicrobial resistance, necessitating a focused search for important therapeutic bioactive compounds from natural sources. Objective: To investigate the antimicrobial potential of leaf extracts and fractions of Ficus vogelii and Telfairia occidentalis against wound clinical isolates. Materials and Methods: Pulverized plant leaves were screened for the presence of phytochemicals. Extraction of ground leaves was by cold maceration with methanol, and fractions were obtained by partitioning into hexane, ethyl acetate and methanol. Antibiogram of clinical isolates was determined via disc diffusion method. Antimicrobial susceptibility of test isolates was determined by agar-well diffusion while minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were determined by microbroth dilution assay. Time-kill assay of the methanol fraction of plants was carried out using the viable count technique. Results: Alkaloids, anthraquinones, cardiac glycosides, flavonoids, saponins, steroids, tannins, and terpenoids were the phytochemicals detected. The plant extracts and fractions had appreciable inhibitory effects against the multi-drug resistant test organisms, with MIC and MBC values ranging from 3.125 to 12.5 mg/mL and 12.5 to > 50 mg/mL, respectively. A total kill of the organisms was achieved at 24 hours at 3.125mg/mL and 6.25 mg/mL of methanol fractions of both plants. Conclusion: Ficus vogelii and Telfairia occidentalis contain bioactive compounds that can be developed into standard chemotherapeutics for the management and treatment of wound infections.